Implementasi Pendekatan Home Visit Upaya Mengatasi Problematika Pembelajaran Daring pada Siswa Sekolah Dasar Di Masa Pandemic Covid – 19 - Abdul Sholeh (Jurnal Bidang Pendidikan Dasar, 2021)
Prevention of the Covid 19 virus is carried out by various parties, including the government stipulating the implementation of education policies in the emergency period of the spread of the Covid 19 virus with steps in the form of learning to be carried out at home using the online method. The implementation of online learning has strengths, challenges and problems/ obstacles. for students, teachers, and parents of students. This study aims to describe the implementation of the home visit approach as an effort to overcome the problems of online learning for elementary school students during the Covid 19 Pandemic. The research method used is qualitative through surveys, observations, interviews via video calls and literature. The application of the home visit approach is carried out through the planning, implementation and evaluation stages with the results of the research, namely that there is intensive communication and cooperation between teachers, students and parents, students are more guided and assisted in learning so that they can overcome learning difficulties. As for the benefits of the research results, namely solving problems of online learning for students, teachers and parents and forging intensive relationships to make learning programs successful in schools.